Mucosectom2-short blade for safe and efficient endoscopic submucosal dissection of colorectal tumors - Okamoto, Koichi; Kitamura, Shinji; Muguruma, Naoki; Takaoka, Toshi; Fujino, Yasuteru; Kawahara, Yoshiro; Okahisa, Toshiya; Takayama, Tetsuji (Endoscopy, 2013)
Background and study aims: Endoscopic submucosal dissection (ESD) in the colon has rapidly come into widespread use. However, as complications such as bleeding and perforation often occur, and the procedure time is longer for ESD than for endoscopic mucosal resection (EMR), development of safer and more reliable devices are required especially for colorectal ESD. We report on a new device, the Mucosectom2-short blade (M2-SB) for colorectal ESD and describe its safety and efficacy.Patients and methods: The study included 30 patients with lesions diagnosed as colorectal tumor: a nongranular-type laterally spreading tumor (LST) larger than 20 mm or a granular-type LST larger than 30 mm, or lesions that were evaluated as being difficult to remove even by piecemeal EMR. Results: All lesions were resected en bloc using this new device, with free lateral and vertical margins. The procedure time was 61 minutes and there was no bleeding or perforation related to the procedure. Conclusion: The M2-SB seems to be a safe and efficient tool for colorectal ESD.